Fluorometric response of photosynthetic microorganism consortium as potential bioindicator for heavy metals detection in water - Khishamuddin N.A.; Shing W.L.; Kin C.M.; Niu V.B.W. (Thai Society of Higher Eduation Institutes on Environment, 2023)
bioindicator; cadmium; cell organelle; concentration (composition); copper; detection method; microorganism; photosynthesis